Unusual suspects: Real-time physiological evaluation of stressors during laparoscopic donor nephrectomy - Wilson, Claire; Chahine, Saad; Cristancho, Sayra; Aquil, Shahid; Mandurah, Moaath; Levine, Max; Sener, Alp (Canadian Urological Association Journal, 2020)
Introduction: The purpose of this study was to document the variability of faculty surgeon electrodermal activity (EDA) peaks during laparoscopic donor nephrectomy (LDN) to determine the effect of case difficulty and learner expertise on the stress response. Methods: EDA for a single faculty surgeon was captured over 15 LDN cases using an Empatica E4 wristband. During each case, one of three transplant fellows (novice, intermediate, or expert level LDN expertise) participated. Difficulty was rated preoperatively as “low/moderate/high” by the faculty. EDA peaks were collected and analyzed; the frequency and magnitude of EDA peaks, case difficulty, and fellow expertise were compared using a two-way factorial ANOVA. Results: The main effects of learner expertise (F[2, 308]=11.27, p<0.001) and difficulty rating (F[2, 414]=15.13, p<0.001) were significant. The interaction between difficulty and expertise on faculty EDA peaks was also significant (F[3, 391]=14.29, p<0.001). The novice fellow resulted in higher faculty EDA levels compared to intermediate and expert fellows on low-difficulty cases, but not moderate- or high-difficulty cases. Conclusions: This is the first report examining faculty surgeon EDA across cases of varying difficulty and varying learner expertise during a high-stakes operation. EDA levels were inversely proportional to the expertise of the learner and case difficulty, suggestive of a significant impact of learner autonomy on faculty stress response.